White Paper on Indian Railways - Planning Commission (Planning Commission, 1952)
The first railway line was constructed in India nearly a hundred years back, primarily, on considerations of military necessity. The maintenance and expansion of British authority in India demanded an inexpensive and expeditious mode of transport for the movement of troops and military equipment. The exploitation of the natural resources of the country to assist the expansion of British industrial production was also an additional consideration. Though the construction of about 200 miles of railway line linking the three port towns of Calcutta, Bombay and Madras with the immediate hinterland was sanctioned in 1845, a railway policy for the country was formulated only with the acceptance of the well-reasoned case presented by Lord Dalhousie in 1853 for linking up the principal cities of India in the interests of social, political and commercial advantages. The wisdom of the policy advocated, particularly.
Government of India Ministry of Railways
Government of India Ministry of Railways